Nanopackaging Nanotechnologies and Electronics Packaging - Morris, James E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents a comprehensive overview of nanoscale electronics and systems packaging, and covers nanoscale structures, nanoelectronics packaging, applications of nanoparticles, graphene, carbon nanotubes and nanowires in packaging, and offers a roadmap for future trends. Composite materials are studied for high-k dielectrics, resistors and inductors, electrically conductive adhesives, conductive "inks," underfill fillers, and solder enhancement. Now in a second edition, Nanopackaging is an important reference for industrial and academic researchers, as well as practicing engineers seeking information about latest techniques. 12 new chapters address carbon nanotubes and nanowires, fabrication and properties of graphene, graphene for thermal cooling of microelectronics and for electrical interconnections, packaging of post-CMOS nanoelectronics, environmental and health effects of nanopackaging technologies, and more. This book is an ideal reference for researchers, practicing engineers, and graduate students who are either entering the field for the first time, or are already conducting research and want to expand their knowledge in the field of nanopackaging.
Nanopackaging: Nanotechnologies and Electronics Packaging -- Modelling Technologies and Applications -- Advances in Delamination Modeling: Continuum Aspects -- Advances in Delamination Modeling: Atomistic Aspects -- Soft Mold Nano-imprint: Modeling and Simulation -- Nanoparticle Properties -- Nanoparticle Fabrication -- Nanoparticle-based High-k Dielectric Composites for Embedded Capacitors -- Nanostructured Materials for Embedded Resistors -- Nanogranular Magnetic Core Inductors: Design, Fabrication and Packaging -- Nanoparticles in Isotropic Conductive Adhesives -- Nano materials in Anisotropic Conductive Adhesives (ACAs) -- Nanoparticles in Microvias -- Silver Nanoparticles for Inkjet Printed Conductive Structures in Electronic Packaging -- A Study of Nano Particles in SnAg-Based Lead Free Solders -- Nano-Underfills for Fine Pitch Electronics -- Carbon Nanotubes: Synthesis and Characterization -- Characteristics of Carbon Nanotubes for Nanoelectronic Device Applications -- High Electromagnetic Shielding of Plastic Transceiver Packaging Using Dispersed Multiwall Carbon Nanotubes -- Properties of 63Sn-37Pb and Sn-3.8Ag-0.7Cu Solders Reinforced with Single-Wall Carbon Nanotubes -- Carbon Nanotubes for Thermal Management of Microsystems -- Nanowires in Electronics Packaging -- Nanowire ACF for Ultrafine pitch Flip-Chip Interconnection -- Synthesis and Optical Characterization of CVD Graphene -- Characterization of electronic, electrical, optical and mechanical properties of grapheme -- Graphene for Thermal Cooling of Microelectronics -- Carbon Interconnects -- Design and Development of Stress-Engineered Compliant Interconnect for Microelectronic Packaging -- Nanosensors for Electronics Package Reliability -- Applications of Bio-Nanotechnology to Electronics Packaging -- Flip Chip Packaging for Nanoscale Silicon Logic Devices: Challenges and Opportunities -- Nanotechnology Health, Safety, Environment Overview.
Keywords: Nanotechnology; Electronics; Electrochemistry; Nanotechnology; Electronics and Microelectronics, Instrumentation; Electrochemistry